Constructing the 'ideal' family in family centred practice: challenges for delivery. - Dodd, Jennifer; Saggers, Sherry; Wildy, H. (Routledge, 2009)
Family centred practice positions families as the key decision makers, central to, and experts in, the wants and needs of their child. This paper discusses how families interviewed for a Western Australian study describe their relationships with a range of allied health professionals in the paediatric disability sector. The allied health professionals, in turn, describe how they characterise the role of families caring for children with disabilities. We argue that the successful implementation of family centred principles in service delivery need to move beyond the individualising of responsibility and acknowledge the structural and systemic limits to family centred practice as well as the social complexity within which diverse families live.